Culture as a cure Assessments of patient safety culture in OECD countries - de Bienassis, Katherine (OECD Publishing, 2020)
While health care quality has been improving on average in OECD members countries, patient safety remains a central priority for policy makers and health care leaders. A growing research body has found that PSC is associated with numerous positive outcomes, including improved health outcomes, improved patient experience, and organisational productivity and staff satisfaction. Tools to measure PSC have proliferated in recent decades and are now in wide-spread use. This report includes findings from OECD countries on the state of the art for measurement practices related to PSC. Overall, measurement of PSC is prevalent across OECD countries, though the application, purpose, and tools vary. International learning and benchmarking has significant potential for better understanding and improvement of patient safety and health care quality
Keywords: Social Issues/Migration/Health